Clinical versus Evidence-based Rehabilitation Options for Post-stroke Visual Impairment. (2nd November 2017) - Hanna, K. L.; Rowe, F. J.
ABSTRACT: The aim of this study was to identify which treatments for post-stroke visual impairment have a supportive evidence base, and which are being used in practice without supportive evidence. A systematic review of the literature reporting on the available treatment options was compared against the visual treatments used in the Vision In Stroke (VIS) study. Treatments were identified for visual field, visual neglect, visual perception and ocular motility disorders. Visual scanning therapies for hemianopia and neglect have an established evidence base. However, a number, such as typoscopes and advice options, have limited detail of their effectiveness and require further research.